Design of sago starch sifting machine with electric motor drive. Issue 1 (1st December 2022) - Widanarti, I; Setiawan, Y; Witdarko, Y; Mangera, Y
Abstract: The purpose of this research is to produce a sago starch sieving machine with an electric motor drive. This study used an experimental method by making and testing a sago starch sieving tool. The starch material used is Dwitrap sago starch. The calculations carried out are the calculation of the pulley speed and the capacity of the tool, while the sieving test was carried out by sifting 5 kg of sago starch which was repeated 3 times. The size of the sieve used is 100 mesh, from the sifting results will be obtained sago starch that passes and does not pass the sieve. In addition, the water content of sago starch was calculated before sieving. The results showed that the sago starch sieving machine with electric motor drive had specifications: length 114 cm, width 74 cm, overall height 90 cm. This tool consists of 4 main components, namely, the frame, the output, the sifter, and the electric motor. The resulting pulley speed is n1 1, 400 rpm, n2 600 rpm while n3 150 rpm. The working capacity of the machine is 76.75kg/hour. with an average of 4.03 kg of sago starch that passed the sieve and 0.96 kg of which did not pass. The water content test on Dwitrap sago starch showed that the water content was still high, namely 16.23%. The high water content in sago starch will greatly affect the sieve results.